The use of carbon isotope ratios to evaluate legume contribution to soil enhancement in tropical pastures - Rao, Idupulapati M.; Ayarza, Miguel Angel; Thomas, Richard J. (Springer, 1994)
Soil carbon distribution with depth, stable carbon isotope ratios in soil organic matter and their changes as a consequence of the presence of legume were studied in three 12-year-old tropical pastures (grass alone Brachiaria decumbens (C4), legume alone Pueraria phaseoloides (C3) and grass + legume) on an Oxisol in Colombia. The objective of this study was to determine the changes that occurred in the13C isotope composition of soil from a grass + legume pasture that was established by cultivation of a native savanna dominated by C4 vegetation. The13C natural abundance technique was used to estimate the amount of soil organic carbon originating from the legume. Up to 29% of the organic carbon in soil of the grass + legume pasture was estimated to be derived from legume residues in the top 0 2-cm soil depth, which decreased to 7% at 8 10 cm depth. Improvements in soil fertility resulting from the soil organic carbon originated from legume residues were measured as increased potential rates of nitrogen mineralization and increased yields of rice in a subsequent crop after the grass + legume pasture compared with the grass-only pasture. We conclude that the13C natural abundance technique may help to predict the improvements in soil quality in terms of fertility resulting from the presence of a forage legume (C3) in a predominantly C4 grass pasture.